2004
DOI: 10.1016/j.jfms.2003.08.007
|View full text |Cite
|
Sign up to set email alerts
|

High viral loads despite absence of clinical and pathological findings in cats experimentally infected with feline coronavirus (FCoV) type I and in naturally FCoV-infected cats

Abstract: Specified pathogen-free cats were naturally infected with FCoV or experimentally infected with FCoV type I. Seroconversion was determined and the course of infection was monitored by measuring the FCoV loads in faeces, whole blood, plasma and/or monocytes. Tissue samples collected at necropsy were examined for viral load and histopathological changes. Experimentally infected animals started shedding virus as soon as 2 days after infection. They generally displayed the highest viral loads in colon, ileum and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
145
1
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(158 citation statements)
references
References 36 publications
10
145
1
2
Order By: Relevance
“…It differs from serotype II FCoV in that it hardly grows in tissue culture (Jacobse-Geels & Horzinek, 1983); however, oral administration of faeces or gut homogenates from shedding cats leads to intestinal infection and monocyte-associated viraemia (Meli et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It differs from serotype II FCoV in that it hardly grows in tissue culture (Jacobse-Geels & Horzinek, 1983); however, oral administration of faeces or gut homogenates from shedding cats leads to intestinal infection and monocyte-associated viraemia (Meli et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, two FCoV biotypes have been distinguished: feline enteric coronaviruses (FECVs), which are endemic in cat populations and generally not associated with clinical disease, and FIP viruses (FIPVs), which might arise from endemic FECVs either as an in vivo mutation or as virulent strains and are responsible for the development of FIP (Vennema, 1999;Brown et al, 2009;Pedersen et al, 2009;Chang et al, 2010). Regardless of the development of FIP, FCoV spreads from its initial site of infection within the intestine via monocyte-associated viraemia (Gunn-Moore et al, 1998;Kipar et al, 1999Kipar et al, , 2005Meli et al, 2004) and can replicate within monocytes in healthy cats (Can-Sahna et al, 2007). The pathogenesis of FIP is not fully understood, but it has been shown that a monocyte-triggered vasculitis, in association with systemic monocyte and endothelial cell activation, represents the crucial event (Kipar et al, 2005), probably in combination with some antibody-mediated enhancement and complement activation (Dewerchin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations